Study of menopausal symptoms and perception about menopause among postmenopausal women residing in Mechinagar municipality - Nepal, Bindu; Acharya, Aashish (Nepal Journal of Health Sciences, 2023)
Introduction: Menopause is the end of a woman’s menstrual cycles and an important biomarker of both fertility loss and menopausal symptoms. Menopausal health has received limited attention in developing countries until more recent times. As women’s status in society continues to improve, an increasing number of them are now seeking assistance for their menopausal issues. Objective: To determine prevalence of menopausal symptoms and assess the perspectives of postmenopausal women regarding the menopausal experience. Methods: A cross-sectional descriptive study was conducted on 162 women in postmenopausal phase, specifically those aged between 45 and 60 years, residing in Mechinagar municipality. The study included women who had not had a menstrual cycle in the previous year. The study employed convenient sampling technique. The study applied the Menopause Rating Scale (MRS) to find presence of menopausal symptoms and its severity. Results: The participants had an average age of 55.72 (SD ± 4.401 ) years. The mean age for menopause was of 47.17 years, with a standard deviation of ±4.473. Among the women surveyed, the most frequently reported menopausal symptoms included somatic symptoms such as heart discomfort, urogenital symptoms like bladder problems, hot flushes, joint and muscular pain, , and psychological symptoms such as irritability. Majority 143 (88.3%) of the respondents had MRS score of less than 16. There was a predominantly positive perception of menopause. Conclusion: The findings of this study indicated a high prevalence of menopausal symptoms, but these symptoms were generally of low severity. There was at least one menopausal symptom reported by each postmenopausal woman who participated in this study.